Digital Leadership Influencing the Capabilities of Early Childhood Education Organizations in School Mover I Bandung - Mulyaniapi, Tepi; Permana, Johar; Soemarto, Soemarto; Nurdin, Diding (Universitas Pendidikan Indonesia, 2024)
The study aims to investigate the challenges and issues arising from the impact of digital leadership and organizational capabilities on Early Childhood Education (ECE) School Mover in Bandung City. This includes understanding how these factors may hinder or enhance the educational environment in such institutions. This research examines the influence of digital leadership and organizational capabilities in Early Childhood Education (ECE) School Mover in Bandung City. The author used the Structure Equation Model (SEM) in conjunction with quantitative methods on a sample of 238 participants. Results indicate that all indicators on both variables effectively reflect the latent variables, and show a strong level of validity. These findings underscore the significance of digital leadership in enhancing educational organizational capabilities. Even though ECE is part of School Mover, with the vision